2019
DOI: 10.1093/aje/kwz165
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Oxford WebQ Online 24-Hour Dietary Questionnaire Using Biomarkers

Abstract: The Oxford WebQ is an online 24-hour dietary questionnaire that is appropriate for repeated administration in large-scale prospective studies, including the UK Biobank study and the Million Women Study. We compared the performance of the Oxford WebQ and a traditional interviewer-administered multiple-pass 24-hour dietary recall against biomarkers for protein, potassium, and total sugar intake and total energy expenditure estimated by accelerometry. We recruited 160 participants in London, United Kingdom, betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 46 publications
3
124
1
1
Order By: Relevance
“…In the present study, BMI was calculated from standardised measurements of weight and height, whereas previous studies used self-reported weight and height. Therefore, it is possible that adjusting for BMI in this study explained a larger proportion of the observed associations; high BMI has been consistently shown to be associated with a large increase in the risk of gallbladder disease in both observational and genetic studies [ 18 – 20 ]. We observed a novel association between poultry intake and gallbladder disease, though additional research is needed to assess this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, BMI was calculated from standardised measurements of weight and height, whereas previous studies used self-reported weight and height. Therefore, it is possible that adjusting for BMI in this study explained a larger proportion of the observed associations; high BMI has been consistently shown to be associated with a large increase in the risk of gallbladder disease in both observational and genetic studies [ 18 – 20 ]. We observed a novel association between poultry intake and gallbladder disease, though additional research is needed to assess this association.…”
Section: Discussionmentioning
confidence: 99%
“…Participants recruited after 2009, as well as participants who provided UK Biobank with an email address and agreed to be re-contacted, were additionally invited to complete the Oxford WebQ [ 18 ], an online 24-h recall questionnaire. Participants were asked to select how many portions of each food item they consumed over the previous 24 h, enabling calculation of mean grams per day by multiplying frequencies of consumption by standard portion sizes.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, dietary information was obtained via repeated 24-h recall questionnaires where available which have been shown to be more accurate than food frequency questionnaires for commonly consumed foods [37]. We used the data from all completed questionnaires to correct for within-person variation in diet.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Online versions of "traditional" dietary assessment methods have been developed, but errors and biases remain. Validation studies of a range of online 24-h recall and food diary tools have shown the same problems as their paper-based equivalents; misreporting, portion size estimation, accurately matching foods consumed to foods in composition databases, and high participant burden (16,20,21). With the best methods currently available, on paper or online, a maximum of 80% of true intake can be captured and there are systematic differences in the 20% of food intake missing (10,15).…”
Section: Introductionmentioning
confidence: 99%